The use of functional approach to assessing secondary four express students' narrative writing - Png, Jessie Lay Hoong. (2008)
This study explores the use of the Functional Approach in assessing the writing of Upper Secondary School students in Singapore. It is felt that the current system of assessing Upper Secondary students' writing is flawed primarily because it does not focus on the specific structural and linguistic requirements demanded by the various genres of writing, such as the narrative and argumentative genres. This study therefore sets out to test the effectiveness of an alternative approach to assessing students' writing using the Functional Approach (Macken and Slade, 1993) which focuses on particular genres of writing. The specific genre that this study focuses on is the narrative.